Exploring the Role of Spiritual Groups in Empowering and Supporting Cancer Patients - Elfrida, Solha; Kusumawaty, Ira; Yunike, Yunike; Sri Ananingsih, Esti; Monalisa, Monalisa; Inastyarikusuma, Tarrinni; Podojoyo, Podojoyo (Yayasan Rumah Ilmu Professor, 2024)
People with cancer not only need medical care but also emotional and spiritual support to face the challenges of their disease. This study aims to explore the role of spiritual groups in empowering and supporting cancer patients and measuring the impact of spiritual interventions on patient well-being. The research uses a qualitative approach with a case study method. Data was collected through in-depth interviews, participant observation, and documentation analysis from three spiritual groups in South Sumatra that actively support cancer patients. The results show that local spiritual groups are important in supporting cancer patients through various means. These groups provide emotional support, spiritual empowerment, and a sense of community that helps patients feel more connected and cared for. Group prayer sessions, meditation and spiritual counselling organized by the group provide inner peace and reduce levels of anxiety and depression in patients. Spiritual groups also help patients find meaning and purpose in their fight against cancer, which strengthens their zest for life and motivation to undergo treatment. Active participation in spiritual activities has been proven to improve the quality of life of cancer patients. Patients report feeling more positive, increased gratitude, and closer relationships with their family members and communities. Spiritual groups also serve as a bridge between patients and other resources and social and medical assistance, which can lighten the patient's overall burden. This research concludes that spiritual groups are crucial in empowering and supporting cancer patients. Structured and ongoing spiritual support can improve patients' emotional and spiritual well-being, contributing to their holistic recovery. Integration of spiritual support in cancer treatment programs is highly recommended. Collaboration between healthcare providers and local spiritual groups can strengthen support systems for cancer patients, ensuring that they receive comprehensive and ongoing care.